(untitled) (International Journal of Business Innovation, 2023)
The study determines the various types of budgets used by SMEs and determines the influence of budgetary control on financial performance of SMEs in Osun State, Nigeria. The sampling method used was purposive, while semi closed ended questionnaires were sent to 250 SME operators/managers to collect information on the different types of budgeting used, budget control, and financial performance of their SMEs. A total of 200 completed questionnaires were completed and returned to researcher. The results of simple percentage reveal that approximately 60% of small businesses used budgets, while approximately 40% of small businesses do not. It was further revealed that most SME operators frequently used types of budgets such as sales budget and cash budget, capital budget, and inventory budget while the least frequently used budgets were marketing budget and personnel by the SMEs in Osun State Nigeria. The results also confirm that the majority of SMEs review their budgets, prepare their budgets, and review their financial performance on a monthly basis. Additionally, regression analysis of the model showcases that budgetary control has a significant influence on financial performance of SMEs. This implies that budget control is a powerful management tool that helps managers carefully analyze all existing operations, and assists SMEs to improve financial performance and sustainability amid global competitive environment. Subsequently, the study recommends that SMEs should organize seminars, workshops, and short courses on the different types of budgets available to make effective decisions terms in terms of an organization’s desired performance in pursuing short-term goals. This allows small businesses to accelerate their operational plans and focus on achieving their desired goals.